A glance at the gut microbiota and the functional roles of the microbes based on marmot fecal samples - Chen, Chuizhe; Chen, Shu; Wang, Bo (Frontiers in Microbiology, 2023)
To obtain full details of the gut microbiota, including bacteria, fungi, viruses and archaea, in marmots, we created a comprehensive database of bacterial, fungal, viral, and archaeal genomes and aligned metagenomic sequences (determined based on marmot fecal samples) against the database. We delineated the detailed and distinct gut microbiota structures of marmots. A total of 5,891 bacteria, 233 viruses, 236 fungi, and 217 archaea were found. The dominant bacterial phyla were Firmicutes, Proteobacteria, Bacteroidetes and Actinomycetes. The viral families were Myoviridae, Siphoviridae, Phycodnaviridae, Herpesviridae and Podoviridae. The dominant fungi phyla were Ascomycota, Basidiomycota and Blastocladicmycota. The dominant archaea were Biobacteria, Omoarchaea, Nanoarchaea and Microbacteria. Furthermore, the gut microbiota was affected by host species and environment, and environment was the most important factor. There were 36,989 glycoside hydrolase genes in the microbiota, with 365 genes homologous to genes encoding β-glucosidase, cellulase, and cellulose β-1,4-cellobiosidase. Additionally, antibiotic resistance genes such as macB, bcrA and msbA were abundant. To sum up, the gut microbiota of marmot had population diversity and functional diversity, which provides a basis for further research on the regulatory effects of the gut microbiota on the host. In addition, metagenomics revealed that the gut microbiota of marmots can degrade cellulose and hemicellulose.